Frontiers in Materials Processing, Applications, Research and Technology Select Proceedings of FiMPART 2015 - Muruganant, M.; Chirazi, Ali.; Raj, Baldev; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This volume comprises the select proceedings of FiMPART 2015. The volume covers advances in major areas of materials research under one umbrella. This volume covers all aspects of materials research, processing, fabrication, structure/property evaluation, applications of ferrous, non-ferrous, ceramic, polymeric materials and composites including biomaterials, materials for energy, fuel cells/hydrogen storage technologies, batteries, super-capacitors, nano-materials for energy and structural applications, aerospace structural metallic materials, bulk metallic glasses and other advanced materials. The book will be useful to researchers, students, and professional working in areas related to materials innovation and applications.
1. String-Like Fiber Dust Occurrence in Crush Cutting of Stacked Liner Boards -- 2. Phase Transformation of Amorphous Rice Husk Silica -- 3. Analysis of Nano/Micro Bimodal SUS316L Powder Behavior -- 4. Tensile Deformation Behavior of Al-Rich Ferritic Steels for Advanced Light Water Reactors -- 5. A Study on Precipitation Behaviour of A356 Alloy by Ultrasonic Velocity Measurements -- 6. Synthesis of Superhard Lightweight Composites and Improvement of their Properties via Chemical Processing -- 7. Structural and Chemical Variations Induced by Thermomechanical Cycling in Shape Memory Actuators -- 8. Enhancement of Thermal Conductivity on Ternary Eutectic Fatty Acid as Phase Change Material (PCM) by Various Treated Exfoliated Graphite Nanoplatelets (XGNP) -- 9. Elements Diffusion in Brazing Seam of High Volume Fraction Sicp/6063Al Matrix Composites -- 10. Functionally Graded Cemented Carbides Elaboration by Imbibition Process Â€" Better Understanding of Liquid Migration and Homogenization Mechanisms for an Improved Process -- 11. Water Analogy Experiment on The Multi-Concentration Pouring Process of A 585 Ton Steel Ingot -- 12. Ferroelectric (Hf,Zr)O2 Thin Films for High Density Non-Volatile Memories -- 13. Advanced System for Nano-Fabrication and Nanomanipulation Based on Shape Memory Alloy -- 14. Synthesis of Aluminium-Graphene Nanocomposite Using Spark Plasma Sintering -- 15. Time-Lapse Correlative 3D Imaging Applied To The Corrosion Study of Az31 Mg Alloy in A Saline Environment -- 16. Welding and Heat Treatment Behaviour of T23 (2.25Cr-1.6W-V-Nb) Steel Tubes in Power Plant Applications -- 17. Solar Performance Analysis of Zrox/Zrc-Zrn/Zr/Ss Spectrally Selective Coating Under Extreme Thermal Environment -- 18. A Comprehensive Study of Hydrogen Redistribution and Embrittlement Prevention in Ferrous Alloys -- 19. Advances in Small Specimen Testing Methods for Characterising Tensile, Creep and Fracture Properties of Materials -- 20. An Approach To Develop Hansel-Spittel Constitutive Equation During ingot Breakdown Operation of Low Alloy Steels -- 21. Development of An Artificial Neural Network Model for CO2 Corrosion Prediction -- 22. Study on The Adhesive Joint Strength of 2060-T8 Al-Li Alloy Single Lap Joint With Different Adhesives -- 23. Mechanical Properties of Ti2Alnb and Ti2Alzr intermetallics: A First Principles Study -- 24. Effects of Micro-Ti Addition on Improving Hot Ductility of Nb-Bearing Ultra High Strength Steels -- 25. Effect of Transition Metals on Thermal Stability of Alâ€'Si Cast Alloys -- 26. Comperative Anaysis of The Fabrication Methods and Structure of The Selected Cnts-Nps Nanocomposites -- 27. Structure and Properties of The Skeleton Microporous Materials With Coatings inside The Pores for Medical and Dental Applications -- 28. Twip Mechanism in Processing of High-Manganese Austenitic Steel -- 29. Impact Behaviour of Super Duplex Stainless Steel Weldments At Sub-Zero Temperatures -- 30. Microstructural Evolution and Strengthening of Stainless Steels During Cold Rolling -- 31. influence of Nickel on The Properties of P91 Flux Cored Wire Weld Metal -- 32. Effect of Cross Â€" Linking Agent on The Thermo Â€" Mechanical Properties of Acrylate Shape Memory Polymer Network -- 33. Exchange Bias and interfacial Magnetic Phenomena in Mechanically Milled Ferromagnetic/Antiferromagnetic Nanocomposites -- 34. Effect of Alloying Additions on The Properties Af-Fecting Shape Memory Properties of Cu-12.5Al-5Mn Alloy -- 35. Preparation of Spherical Fine Metal Powder by Hybrid Waterâ€"Gas Atomization.
Keywords: Materials science; Materials; Manufactures; Materials Science; Materials Engineering; Machines, Tools, Processes